Determinación de áreas con potencial material de áridos para la obra pública de la parroquia el tambo, perteneciente al cantón Catamayo, provincia de Loja - Rodríguez Castro, Trosky Alberto (2016)
The present project is related to the determination of potential areas for the mining of construction materials that will be used for base and sub-base of tracks in the projects carried out by the parish El Tambo. It was developed using 52 aerial photographs at 1:25000 scale, geological maps of Gonzanamá, Loja, Cariamanga and Zaruma at 1:100000 scale and topographic maps of Nambacola, Gonzanamá and Rio Sabanilla at scale 1: 50,000. The collection of information, allowed to obtain the main areas of mining which were based on geology, hydrology, road network and mining concessions; through a corroboration study in field, the areas were discarded in base of three basic conditions (environment, social and cultural heritage), in this way using this process was defined the selected area. The studies made to the area were based on the geological characterization of the deposit, emphasizing the shape of the arid in base of its geometricity, equanticity, sphericity, circularity and roundness, in addition to the tests proved in the laboratory. As a result of this, was delimitated the selected area, which have an area and volume that will provide the necessary material for the realization of the base and sub-base in the different projects that are in charge of the Decentralized Autonomous Government of the Parish El Tambo.